A Low-Duty-Cycle and Congestion-Robust Design of Adaptive Wi-Fi 7 Multi-Link Operation Control Over User Side - Yirong Cheng; Abhishek Sehgal; Kyeong Jin Kim; Neha Dawar; Yuming Zhu (IEEE Access)
Wi-Fi 7 has been developed recently to support new applications such as 4K videos and AR/VR, which demand higher network throughput and lower latency. One of its key features, Multi-link Operation (MLO), enables Wi-Fi 7 to utilize multiple carrier frequencies, enhancing throughput and reducing latency. Recent research has extensively covered MAC-layer architecture and multi-link channel access algorithm design for MLO implementation, but relatively few studies address the power efficiency problem when MLO is implemented in user devices under dynamic traffic conditions. For user devices, power efficiency is critical due to stricter power budgets, and hence, a minimal radio activation time (i.e., duty cycle) is needed. We have devised an adaptive algorithm that dynamically adjusts MLO configurations based on periodic measurements at the MAC/IP layers. Our simulations using the NS-3 platform demonstrate that our approach maintains MLO’s congestion-resistant throughput advantages while significantly reducing the radio’s duty cycle compared to a static MLO mode. This adaptation makes MLO more feasible for power-sensitive user devices.